Instagram Versus Reality: Who Are Actually Plastic Surgeons? - Nikhi P. Singh, MD, MBA; Mary M. Holohan, MD; Cameron Harmon, BS; Kasra N. Fallah, MD; Jeffrey Gross, MD; Aadarsh Patel, MD; Carter J. Boyd, MD, MBA; Matthew R. Greives, MD, MS; Jorge de la Torre, MD, MSHA; Gayle Gordillo, MD; Timothy W. King, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Instagram has become one of the most powerful marketing tools available to plastic surgeons because patients have increasingly turned to online resources to find physicians. Within, we review the online presence of self-ascribed plastic surgeons in the United States to identify potential misinformation and dishonest advertising. Methods:. The Inflact database was queried for the search terms: “plastic surgeon/surgery,” “plastic and reconstructive surgeon/surgery,” “aesthetic surgeon/surgery,” and “cosmetic surgeon/surgery.” US physician account information, history of medical training, American Board of Plastic Surgery (ABPS) certification status, and posts were reviewed. Results:. In total, 1399 physicians practicing within the United States were identified. Most attended medical school in the United States (93%), a minority received integrated plastic surgery training in the United States (14%), and the majority attended general surgery residency in the United States (57%) followed by independent plastic surgery residency in the United States (50%). Altogether, 1141 individuals were explicitly listed as “plastic surgeons” on Instagram, nearly a quarter of these (325 individuals, 28%) were not certified by the ABPS, and nearly a fifth (251 individuals, 22%) received no training in plastic surgery. Conclusions:. Nearly one-third of “plastic surgeons” on Instagram are not certified through the ABPS. This is detrimental to the reputation of plastic surgery and has the potential to create broader consequences and may lead to patients mistakenly receiving care from unqualified physicians. It is paramount that plastic surgeons create a united front against such endeavors through advocacy efforts within the American Society of Plastic Surgeons.